Dynamic Complement Protein Changes in Aqueous Humor and Plasma of Patients With Retinal Vein Occlusion During Ranibizumab Treatment - Guo T; Zhao Y; Liang S; Wang J; Liu H; Zhou Y; Xu H; Chen Z (Journal of Inflammation Research)
Tingting Guo,1,2,* Yanying Zhao,2,3,* Shengnan Liang,2,3 Jie Wang,2 Hengwei Liu,2 Yufan Zhou,2 Heping Xu,3– 5 Zhongping Chen1– 3,6 1Aier Eye Hospital, Jinan University, Guangzhou, People’s Republic of China; 2Changsha Aier Eye Hospital, Changsha, People’s Republic of China; 3Aier Academy of Ophthalmology, Central South University, Changsha, People’s Republic of China; 4Aier Institute of Optometry and Vision Science, Aier Eye Hospital Group, Changsha, People’s Republic of China; 5The Wellcome-Wolfson Institute for Experimental Medicine, School of Medicine, Dentistry and Biomedical Sciences, Queen’s University Belfast, Belfast, UK; 6School of Stomatology and Ophthalmology, Xianning Medical College, Xianning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhongping Chen; Heping Xu, Email chenzhongping@csu.edu.cn; heping.xu@qub.ac.ukPurpose: To assess dynamic changes of complement protein in aqueous humor (AH) and plasma of retinal vein occlusion (RVO) patients during ranibizumab treatment, and to explore the differential expression of complement proteins in branch retinal vein occlusion (BRVO) and central retinal vein occlusion (CRVO).Patients and Methods: This prospective, consecutive case series study collected AH and plasma samples from 27 RVO patients at baseline, 1 and 2 months after ranibizumab treatment, including 19 BRVO and 8 CRVO patients. The concentrations of 13 complement proteins and vascular endothelial growth factor A (VEGF-A) were measured using Luminex® × MAP® technology.Results: During ranibizumab treatment, a reduction in the levels of C1q (p < 0.001), C2 (p = 0.030), C4 (p = 0.001), C4b (p = 0.026), C3b/iC3b (p < 0.001), C5 (p = 0.007), C5a (p = 0.005), CFD (p = 0.022), CFH (p < 0.001), and CFI (p < 0.001) in AH was observed. No significant changes were observed in the plasma levels of all measured factors. At baseline, CRVO had higher levels of C4 (p = 0.003), C4b (p < 0.001), C3b/iC3b (p < 0.001), C5 (p = 0.020), C5a (p = 0.007), CFD (p = 0.002), CFH (p < 0.001), and CFI (p < 0.001) in AH compared to BRVO.Conclusion: Ranibizumab treatment reduced the intraocular but not circulating activation of classical and alternative complement pathways in RVO patients. Differences in intraocular complement proteins were observed between BRVO and CRVO patients, which may reflect different pathogenesis.Keywords: retinal vein occlusion, complement protein, aqueous humor, plasma